2019
DOI: 10.1590/1984-70332019v19n1a06
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fusarium ear rot and fumonisin contamination in testcrosses of a maize biparental population

Abstract: Fusarium ear rot (FER) negatively affects maize production worldwide and poses a serious threat to human health for producing mycotoxins. The objectives of our study were to assess the factors affecting FER and fumonisin contamination in testcrosses of a maize population. In the trials, seeds of 191 testcrosses of IBMSyn4, 11 checks and 2 replications of parental lines (a total of 216 hybrids) were sown in three environments, in 2014 and 2015. FER disease intensity (DI), fumonisin contamination (FUMc) and numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Similarly, Cao et al (2022) found strong genotypic correlation (r g = 0.85) between FUM and FER severity after kernel inoculation. Based on this, selection for FER-resistant lines would indirectly reduce fumonisins accumulation (Maschietto et al, 2017;Galićet al, 2019). However, our analysis also revealed the existence of one specific QTL for FUM (qFER12, PVE = 8%) on chromosome 5 (Figure 2) and one for DON (qGER12, PVE = 15%) on chromosome 9 (Figure 3), which were identified as independent MQTL for these traits.…”
Section: Figuresupporting
confidence: 55%
“…Similarly, Cao et al (2022) found strong genotypic correlation (r g = 0.85) between FUM and FER severity after kernel inoculation. Based on this, selection for FER-resistant lines would indirectly reduce fumonisins accumulation (Maschietto et al, 2017;Galićet al, 2019). However, our analysis also revealed the existence of one specific QTL for FUM (qFER12, PVE = 8%) on chromosome 5 (Figure 2) and one for DON (qGER12, PVE = 15%) on chromosome 9 (Figure 3), which were identified as independent MQTL for these traits.…”
Section: Figuresupporting
confidence: 55%
“…Although the genotypic variances were quite similar for both landraces, PE showed higher genotype × environment variance resulting in a slightly higher H 2 for KE (Table 1). A large effect of the environmental conditions on ear rot resistance has been reported several times in the literature (Giomi et al 2016;Han et al 2018;Galić et al 2019;Morales et al 2019). Therefore, it is important to phenotype lines for GER resistance in multi-environmental trials.…”
Section: Variation For Ger Severity and Agronomic Traits In European mentioning
confidence: 99%
“…Besides this, the GRMZM2G060216 gene refers to the transcription factor LG2, which is related to systemic acquired resistance by the salicylic acid-mediated signaling pathway (Chen et al 2012). Galić et al (2019) in a study to assess the factors affecting Fusarium ear rot and fumonisin contamination of maize, identi ed genes that can confer resistance, and found genes that code for NAC transcription factor.…”
Section: Discussionmentioning
confidence: 99%